PSIKOLOGI TOKOH AYAH DALAM NOVEL NAK, PANGGIL AKU AYAH KARYA ASTER PUTIH (KAJIAN ANALISIS ISI) - Sumiharti Sumiharti; Mona Puspita Karlina Sitorus (Universitas Batanghari, 2022)
This research aims to describe the psychology of father’s character. This research is a qualitative descriptive. The data is in the form of sentence quotations in which there is a form of inner conflict in Father’s character. The approach used in this research is a Content Analysis Study. Based on the results of data analysis, it can be concluded that: 1. The form of near-approaching inner conflict is contained in 45 quotes, among others; Dengan takjub Ayah Tiri memandang ke arah saya, wajahnya penuh dengan kegembiraan. Tak henti-hentinya ayah berkata “Patut, sangat patut sekali!”. Sejak awal beliau menolak mempunyai anak sendiri, beliau berkata kami ini adalah anak kandungnya. Dan Ayah bersyukur ternyata Ayah sejauh ini berhasil mendidik kalian,” papar Ayah tiriku dengan matanya yang kian membasah. 2. The form of inner conflict of the being away aspect is contained in the quote: Namun, hanya karena sebatang pipa rokok, ayah tiri telah memberikan saya satu tamparan yang sangat keras. Ketika saya menyerahkan pipa itu kehadapan Ayah tiri, beliau menerimanya dengan tangan gemetaran dan tak lupa beliau memberi saya tamparan keras, lalu kedua matanya berlinangan air mata. Ia tak mau menganggap ayah tirinya sebagai ayah, apalagi untuk memanggil “Ayah” Of the two conclusions, the inner conflict of the near-approach aspect is found more 45 quotations than the inner conflict of being away there are 24 quotations